1997
DOI: 10.1897/1551-5028(1997)016<0430:iacoma>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Microtox®-Active Components From Aircraft De-Icing/Anti-Icing Fluids

Abstract: Abstract-The goal of this project was to isolate and identify individual components from aircraft de-icing/anti-icing fluids (ADAFs) through a toxicity-based bioassay analysis. A Microtox bioassay fractionation scheme was used to isolate a number of active fractions from ADAFs. Active fractions were identified using multiple spectral techniques, including nuclear magnetic resonance, gas chromatography-mass spectrometry, liquid chromatography-mass spectrometry, and ultraviolet characterization. The primary Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 6 publications
1
32
0
Order By: Relevance
“…Previous studies have demonstrated that BT is toxic to luminescent bacteria and aquatic organisms, including plants, daphnia, and fish, with effective concentrations at mg L À1 level (Cancilla et al, 1997(Cancilla et al, , 2003Cornell et al, 2000;Pillard et al, 2001;Kadar et al, 2010;Seeland et al, 2012). For example, the acute (96 h) median lethal concentration (LC 50 ) value for fathead minnows (Pimephales promelas) was approximately 65 mg L À1 (Pillard et al, 2001).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Previous studies have demonstrated that BT is toxic to luminescent bacteria and aquatic organisms, including plants, daphnia, and fish, with effective concentrations at mg L À1 level (Cancilla et al, 1997(Cancilla et al, , 2003Cornell et al, 2000;Pillard et al, 2001;Kadar et al, 2010;Seeland et al, 2012). For example, the acute (96 h) median lethal concentration (LC 50 ) value for fathead minnows (Pimephales promelas) was approximately 65 mg L À1 (Pillard et al, 2001).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The acute toxicity EC 50 or LC 50 of BTs to aquatic organisms (Microtox bacteria, fathead minnow and water flea) are in the range of 0.72e118 mg/L (Cancilla et al, 1997;Pillard et al, 2001). BT has been shown to exhibit antiestrogenic activity in vitro in a yeast assay but not in vivo to fish (Harris et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Benzotriazoles are the most toxic components in the ADF, as demonstrated by Microtox ® studies and tests with fathead minnow (Pimephales promelas) and water flea (Ceriodaphnia dubia) [15][16][17]. A value of 0.1 mg/L as the maximum permissible concentration of BT in water reservoirs has been suggested [15].…”
Section: Benzotriazolesmentioning
confidence: 99%
“…A value of 0.1 mg/L as the maximum permissible concentration of BT in water reservoirs has been suggested [15]. The toxicity of TT can result in a decrease in the ability of microorganisms to degrade glycol.…”
Section: Benzotriazolesmentioning
confidence: 99%